(untitled) (Journal of Engineering and Health Sciences, 2024)
Aims: This study investigates the knowledge, attitudes, and practices of mothers caring for children with epilepsy, aiming to explore how these elements influence the care provided. Background: The relationship among mother with Epilepsy Children but the knowledge, attitude and practise care remains the necessary knowledge to effectively manage epilepsy, prevent complications, and improve the overall quality of life for their children, in Paediatric Clinic, Hospital Universiti Sains Malaysia. Design. The cross-sectional study involved 135 mothers who completed a comprehensive questionnaire. Results: The majority of mothers (56.5%) demonstrate a strong understanding of epilepsy and engage in good seizure management practices (60.0%), their attitudes towards the condition are predominantly neutral (84.4%). Additionally, no significant correlation was found between maternal knowledge and educational level (p > 0.05). Conclusions: These is a need for targeted educational interventions to improve attitudes and further support the effective management of epilepsy in children.